Extraction Of Iron (Fe) as A Valuable Metal Content of Nickel Slag Waste - Maryudi, Maryudi; Candra, Syahrul Dwi Adi; Azhar , Muh.; Yahya, Asdarina (Universitas Ahmad Dahlan, 2023)
Nickel slag is a product that is formed at high temperatures to form metal alloys that are stable enough. It becomes a challenge for researchers to find methods for extracting valuable metal content. Leaching is one of the solid-liquid extraction methods that can be applied to separate important elements from a solid material. By using strong acid solvents. Leaching of ferrous metal (Fe) as the main metal in nickel slags was carried out with a 98% 2M sulfuric acid extracting solution. Destruction of the leachate of nickel slag was then conducted to simplify the complex elements in the samples so that they could be easily analyzed. Destruction of nickel slag leachate samples was carried out using a destructive solution in the form of nitric acid. The maximum yield of iron content was obtained at a size of 140 mesh and 60 minutes with an iron content of 19,141 ppm. The minimum yield of iron content was obtained at 80 mesh-30 minutes of leaching with an iron content of 18,433 ppm. The maximum recovery results were obtained at 140 mesh-60 minutes of leaching. Factors that can influence include solid sample size, extracting solution, mineral form in solids, complexity, pH, operating temperature, and leaching time.